As ouvidorias públicas universitárias: autonomia, potencialidades e limites - Santana, Maurino Medeiros de (2017)
This work aims to understand the role of university ombudsmen of the Federal Institutions of Higher Education in the country, its insertion in the context of redemocratization and the challenges regarding its autonomy. In this sense, it is necessary to glimpse how such institutes can contribute to the transparency, greater participation, social control and credibility of the Federal Institutions of Education in Brazil. We start the present study from the understanding of democracy as something fragile and tenaciously avoided for centuries and from the aristocratic conception of democracy in which people and popular sovereignty were treated as irrelevant. The deepening of the theoretical dialogue has led us to a more plural analysis of democracy and to the thesis that there is no incompatibility between elitist democracy and the new architectures of popular participation. These arguments provided an analysis of the Brazilian political reality, converging to the central issue of the expansion of public participation instruments in the country. We demonstrate how the new social actors contributed to the formation of this popular participation architecture and its importance for the advancement of democratic management in the field of public administration. Based on these analyzes, we turn to the central problem of the research, precisely, the study of the university ombudsmen, an important institute of participatory democracy instituted at the Brazilian universities in the 1990s. In this sense, we verified its potentialities and limits and, at same time, we questioned the lack of full ombudsman's autonomy as an instrument of fragility. In the process of this research, we used the existing documentary and bibliographic material on the subject, besides the legislations of the Brazilian university ombudsmen creation and the letters of the meetings of the National Forum of University Ombudsmen. The study concluded that the full autonomy of university ombudsmen is still something to be built and depends on the strengthening of these institutes and on a more democratic process of ombudsman selection through direct election of the university communities. Keywords: Ombudsman; university ombudsman; participation; social control; autonomy; direct election.